Strategies in Coping with Bilingual Instructions Among Science Students in Malaysia - Stapa, Siti Hamin; Suhaimi, Abdul Rauf (European Scientific Journal, ESJ, 2017)
Bilingual instructions are used in classrooms in assisting the learners towards their comprehension of the content delivered. However, the strategies applied by the learners to cope with this kind of instructions are less discussed particularly in the science classrooms. The science courses offered at the National University of Malaysia use bilingual instructions, which are English and Malay. This paper, therefore, aims at investigating the strategies applied by such students. It also aims at examining the students’ perception towards the use of bilingual instructions at the university. 60 low proficient ESL students from the School of Environmental and Natural Resource Sciences, Faculty of Science and Technology, National University of Malaysia were involved in this study. Semi-structured interview was conducted with 4 respondents from the four majors offered by the school in order to gather data. The results revealed that the students mentally translated the bilingual instructions, made inquiries to the lecturers and peers, referred to Google Translation as well as dictionaries in coping with the bilingual instructions. When asked about their preferences, most of them preferred the use of bilingual instructions as it helped them in understanding the science subjects. The study suggests that the students should be equipped with an adequate proficiencies in both languages so that they can successfully understand the lessons using bilingual instructions.